ANALISIS PERBANDINGAN PORTOFOLIO OPTIMAL PADA SAHAM SRI KEHATI DENGAN MENGGUNAKAN MODEL INDEKS TUNGGAL DAN MODEL RANDOM - Maya Novitasari; Heidy Paramitha Devi (INVENTORY: JURNAL AKUNTANSI, 2018)
The purpose of this study is to provide empirical evidence that the determination of a stock portfolio using a single index model can provide optimal returns compared with the determination of stock portfolio using a random model. The sample in this research is 25 shares joined in SRI-KEHATI selected using purposive sampling. The data analysis technique used the average test for two independent samples (Mann Whitney Test (U Test)). The results showed that the determination of the stock portfolio using a single index model can provide optimal return compared to the determination of stock portfolio using random model.